Wideband dielectric properties of silicon and glass substrates for terahertz integrated circuits and microsystems - Nonchanutt Chudpooti; Nattapong Duangrit; Andrew D Burnett; Joshua R Freeman; Thomas B Gill; Chuwong Phongcharoenpanich; Ulrik Imberg; Danai Torrungrueng; Prayoot Akkaraekthalin; Ian D Robertson; Nutapong Somjit (My University, 2021)
Abstract This paper presents a comprehensive study of the optical and electrical dielectric material properties of six commonly-used silicon and glass substrates at terahertz (THz) frequencies, including refractive index, absorption coefficient, dielectric constant and loss factor. The material characterization techniques used in this paper feature THz time-domain transmission and reflection spectroscopy with the measurement frequencies from 0.5 THz up to a maximum of 6.5 THz. Of the six selected dielectric and semiconductor substrates, two are silicon wafers with resistivities ranging from 0.001 to 0.02 Ω-cm. From the measurement results, loss tangents of the selected silicon wafers range from 0.680 to 5.455 and the dielectric constants are from 1.079 to 17.735. The four other wafers are all glass-based substrates: D263 glass, Borofloat 33 glass, fused silica and Sapphire. From the measurements, it is found that the THz dielectric properties vary considerably between the substrate samples e.g. dielectric constants range from 1.925 to 3.207 while loss tangents are from 0.042 × 10 −3 to 0.127. Most of the selected silicon and glass-based substrates are quite useful for many THz applications, e.g., THz integrated circuits (THz ICs), THz microsystem technologies (THz MSTs) and THz system-on-a-chip (THz SoC) and system-on-substrate (SiP).
Keywords: Dissipation factor; Dielectric loss; Terahertz technology and applications